Activin-A, myostatin and interleukin-6 in cancer associated cachexia - Härkönen, Jouni (2017)
Cachexia is a muscle wasting condition associated with multiple different chronic illnesses, such as cancer, diabetes and AIDS. In cancer, approximately 80% of patients with advanced disease have symptoms of muscle wasting, and around 25% of cancer mortality concerns cachexia. Elevated serum levels of different cytokines and TGF-β protein family members, such as Interleukin-6, Myostatin and Activin-A, have been observed in cachetic patients and test animals. However, the mechanistic role and the relative contribution of these molecules to muscle loss in the syndrome have not yet been fully elucidated. In this thesis, the gene-expression levels of Activin-A, Myostatin and Interleukin-6 was assessed with Reverse-Transcriptase quantitative PCR from the tumor and muscle tissue of cachetic C26-tumor-bearing mice to clarify whether they arise from the tumor or are muscle derived. Additionally, transfection of CAGA-luciferase plasmid construct was optimized for the C2C12 murine myoblast cell-line to be utilized in research concerning TGF-β mediated cancer-associated cachexia in vitro. The function of the construct was tested by administration of exogenous Activin-A, with and without its inhibitor, into the C2C12 growth media. This thesis showed a marked increase in the expression levels of Activin-A (inhibin-βA) and IL-6 mRNA in cachexia inducing tumors (C26) when compared to tumors not inducing cachexia (Lewis-Lung-Cancer) (P < 0.001). Additionally, the results show decrease in muscle-derived Activin-A (inhibin-βA) in the cachetic groups (P < 0.05). These results imply that Activin-A and Interleukin-6 are strongly induced in the tumors that produced cachexia in vivo. This work also presents a successful, optimized plasmid transfection protocol for the notoriously transfection resistant C2C12-myoblast cell line. The presented in vitro –method can partially replace animal tests in related settings, when studying the mechanistic effects of cachexia-inducing TGF-β proteins on muscle tissue.